31. UPISketch: New Perspectives - Rodolphe Bourotte (Meta-Xenakis: New Perspectives on Iannis Xenakis’s Life, Work, and Legacies, 2024)
When we consider the needs we may have in the field of electroacoustic music composition, a tool allowing a graphic representation of sound and musical phenomena seems interesting to develop. UPISketch is one of these tools. Part of this chapter focuses on describing the abundance of ideas that the development of such a tool can inspire. UPISketch is a subset of graphical score systems: it is positioned on the question of the graphical representation of quantitative data. It has the potential to update the breakthroughs that Xenakis made through his mathematical approach by making them newly accessible via intuitive graphic interfaces. New possibilities, not yet implemented in the software, will be evoked. Specifically, it is now possible to imagine an extension of the legacy of Xenakis's thinking on sieves and probabilities, in the graphic domain with UPISketch, in a junction that had never been realized with UPIC.